PENGARUH JUMLAH PENDUDUK, PRODUK DOMESTIK REGIONAL BRUTO DAN INFLASI TERHADAP PENERIMAAN PAJAK DAERAH PADA KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH - Sania, Hidayati; Yunita, Eva Anggra; Muttaqin, Ibnu (PERMANA, 2018)
The research aims to knows partially and simultaneously the effect of the number of population, the gross domestic products and inflation toward local tax.Data collection in this research used secondary data. The population in this research amount 35 consist of 29 districts and 6 cities. Sample determination in this research use sample saturated which all population to be sample.The result of this research in the first hypothesis shows the number of population, the gross domestic products and inflation have effect simultaneously toward local tax with significance level of 0,000. The second hypothesis showed the number of population have effect partially toward local tax with significance on the level of 0,001. The third hypothesis showed the gross domestic products have effect partially toward local tax with significance on the level of 0,000. The fourth hypothesis showed inflation have no effect partially toward local tax with significance on the level of 0,915. Keywords: the number of Population, gross domestic products, inflation, local tax.